Nucleotide sequence changes in polyoma virus A gene mutants. - Thomas, T (1981)
The mutational alterations in polyoma virus mutants ts-a and ts-25E which cause their large T-antigens to be thermolabile have been identified. In ts-a, a G leads to A transition at nucleotide 2193 causes the replacement of Ala (GCT) by Thr (ACT). In ts-25E, a G leads to T transversion at nucleotide 2883 causes the replacement of Gly (GGC) by Cys (TGC). Revertants of both mutants have been isolated and shown to have the original nucleotides restored at these positions.